What Exactly is Prohibited in the Field?: A New Suggestion for Understanding the Text and Context of CD 10:20-21 - Jassen, Alex P. (Revue de Qumran, 2011)
This article examines a passage in the Damascus Document’s Sabbath Code that has long eluded full explanation. CD 10:20-21 seems to proscribe an individual from walking through a field on the Sabbath, though the precise details of the law are unclear. The uncertainty regarding the meaning of this passage is due in large part to the apparent textual corruption found in the medieval manuscript of the Damascus Document (MS A). Analysis of this passage begins by examining the textual evidence along with a review of the merits and drawbacks of the three primary explanations proposed by Solomon Schechter, Louis Ginzberg, and Chaim Rabin. This article argues that the full meaning of this passage and its correct emendation can only be understood through exploration of its legal-exegetical use of Isa 58:13. A more nuanced treatment of the exegetical technique of this passage argues in favor of the general interpretation of this passage as a prohibition against traveling through one’s field on the Sabbath to assess what tasks need to be done after the Sabbath. Examination of CD 10:20-21 in the context of its exegetical reformulation of Isa 58:13 brings into sharper focus the textual difficulties and provides a context for the emendation of CD 10:20-21 proposed here.\n4207 \n4207